2017
DOI: 10.1111/jcmm.13291
|View full text |Cite
|
Sign up to set email alerts
|

Short androgen receptor poly‐glutamine‐promoted endometrial cancer is associated with benzo[a]pyrene‐mediated aryl hydrocarbon receptor activation

Abstract: The androgen receptor (AR) poly‐glutamine polymorphism (AR‐Q) was reported to play role in endometrial cancer (EMCA) development, yet controversial. Environmental factors interact with genetic variation have been reported in EMCA. Aerosol toxins, polycyclic aromatic hydrocarbon benzo[a]pyrene (BaP), are EMCA facilitators. This report examined the interplay between AR‐Qs and BaP in EMCA. During analysing patient AR‐Q polymorphism and Aryl hydrocarbon Receptor (AhR) expressions, we found overall survival (OS) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…et al [32]; however, whether an environmental stimulant is involved in AR transactivation remains unknown. Our own previous work showed that the interaction of AR/AhR promoted endometrial cancer progression under AhR ligand (TCDD) treatment [31]. In the present report, we found that there is an alternative ARE, located on the ABCG2 promoter, which could be activated by the xenobiotic receptor AhR, and form an AR/AhR complex.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…et al [32]; however, whether an environmental stimulant is involved in AR transactivation remains unknown. Our own previous work showed that the interaction of AR/AhR promoted endometrial cancer progression under AhR ligand (TCDD) treatment [31]. In the present report, we found that there is an alternative ARE, located on the ABCG2 promoter, which could be activated by the xenobiotic receptor AhR, and form an AR/AhR complex.…”
Section: Discussionsupporting
confidence: 61%
“…NC_018915) (Figure S2). According to previous studies [29,30] and our recent study in AhR [31], we hypothesized that the AR–AhR complex could also be observed in EOC cells. As demonstrated in Figure 1D, using a co-immunoprecipitation (co-IP) assay we were able to observe AR–AhR interactions in the three serous EOC cell lines.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In general, the histological studies were performed as described in previous studies (Hung et al 2014, Chen et al 2018 with some modifications. For general histologic inspection, we treated the tissue sections (2 μM) with H&E or stained the sections with antibodies specific for LDLR and lipoprotein lipase (LPL) with an ABC kit (Vector Laboratories) to enhance the staining signals.…”
Section: Immunohistochemistry and Quantitation Of Staining Scorementioning
confidence: 99%
“…Immunohistochemistry and quantitation of staining score: In general, the histological studies were performed as described in previous studies (Chen, Bao et al, 2018 with some modifications. For general histologic inspection, we treated the tissue sections (2 μM) with hematoxylin and eosin or stained the sections with antibodies specific for LDLR and LPL with an ABC kit (Vector Laboratories) to enhance the staining signals.…”
Section: Targeting Ld Lipid Remodeling For Chemotherapymentioning
confidence: 99%